Anti-xa guided enoxaparin thromboprophylaxis is associated with less thromboembolism than fixed dose dalteparin in trauma patients admitted to intensive care - Ahmad Kloub (16855149) (2025)
Background Venous Thromboembolism (VTE) is a common, preventable complication in trauma. Low-molecular-weight heparin (LMWH) is recommended for VTE prophylaxis (VTEp). We investigated whether switching from fixed-dose dalteparin to anti-Xa-guided enoxaparin prophylaxis reduces VTE without increasing the risk of bleeding among hospitalized trauma patients. Methods This observational study compared injured patients admitted one year before (pre-P) and after (post-P) implementing a new VTEp protocol. The protocol was introduced as a performance improvement project (subcutaneous enoxaparin 30 mg twice daily), with dose calibration to peak plasma Anti-Xa level measured after the 3rd dose. The primary outcomes were the rate of VTE and bleeding. Results After protocol implementation (post-P), 305 patients were compared to 350 pre-protocol patients (pre-P). Anti-Xa levels were measured in 83% of post-P and none in the pre-P. 40% had low levels of anti-Xa, suggesting inadequate prophylaxis, and enoxaparin doses were accordingly increased. 51% attained the desired anti-Xa levels, 9% had higher levels, and LMWH doses were subsequently reduced. VTE incidence after protocol implementation decreased from 4 to 1.3% (OR 0.31; 95% CI 0.1–0.9, P = 0.03) without increasing the bleeding rate. The time intervals between two consecutive PE events were significantly longer after protocol implementation. Among TBI patients, the rate of VTE was lower. However, it did not reach statistical significance. 75% of patients with VTE had low anti-Xa levels, while 20% of those with bleeding had high anti-Xa levels. Conclusion Among adult patients in the trauma ICU, compared to a fixed dose dalteparin, enoxaparin prophylaxis with dose calibration according to peak anti-Xa levels was associated with lower VTE rates without increasing the risk of bleeding. About 40% of patients who received initial enoxaparin doses of 30 mg twice daily had anti-Xa levels suggestive of inadequate prophylaxis. Calibrating LMWH dosing may improve VTEp following traumatic injury. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00068-025-02768-z